2013
DOI: 10.1002/ps.3457
|View full text |Cite
|
Sign up to set email alerts
|

Dosage consistency is the key factor in avoiding evolution of resistance to phosphine and population increase in stored‐grain pests

Abstract: Achieving a consistent fumigant dosage is a key factor in avoiding evolution of resistance to phosphine and maintaining control of populations of stored-grain pests; when the dosage achieved is very inconsistent, there is likely to be a problem regardless of immigration rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…When earlier resistance modellers tackled the issue of polygenic resistance, they tended to use a quantitative genetics approach, based on several assumptions, including that resistance is conferred by a large number of unlinked genes, each of very small additive effect . More recently, modellers have represented multiple genes and their interactions more explicitly, allowing a more detailed and realistic representation of a polygenic basis for herbicide resistance, or other pesticides . This explicit approach also allows for representation of the linkage disequilibrium between alleles that is likely to emerge when very strong selection pressures are driving evolutionary processes, but that is ignored in the ‘traditional’ quantitative genetics approaches.…”
Section: Approaches To Modelling the Evolution Of Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…When earlier resistance modellers tackled the issue of polygenic resistance, they tended to use a quantitative genetics approach, based on several assumptions, including that resistance is conferred by a large number of unlinked genes, each of very small additive effect . More recently, modellers have represented multiple genes and their interactions more explicitly, allowing a more detailed and realistic representation of a polygenic basis for herbicide resistance, or other pesticides . This explicit approach also allows for representation of the linkage disequilibrium between alleles that is likely to emerge when very strong selection pressures are driving evolutionary processes, but that is ignored in the ‘traditional’ quantitative genetics approaches.…”
Section: Approaches To Modelling the Evolution Of Resistancementioning
confidence: 99%
“…When modelling herbicide resistance, spatial heterogeneity in weed and seed densities is likely to be important, as is spatial heterogeneity in the frequencies of resistance alleles. To represent spatial heterogeneity, resistance models can take a relatively simple and implicit approach of just adding variation to parameters likely to vary across space, such as dose, or they can represent space and variation in population density and genetic frequencies more explicitly. Such spatially explicit models can represent variation in space in one dimension, along a transect or gradient, or down through depths in a soil profile, in two dimensions across a field or a landscape of many fields or potentially in all three dimensions.…”
Section: Approaches To Modelling the Evolution Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Rapid responses to drug selection and peaking of the response have been previously observed in Levamisole-selected strains of C. elegans (Lopes et al 2008). Previous research focused on under-dosing has suggested that lower doses (doses below recommended use) may promote the evolution of resistance, especially where the basis of resistance is polygenic (Manalil et al 2011;Shi et al 2013), and that varying the level of under-dosing may affect the rate at which resistance evolves (Busi and Powles 2009). Our data suggest that selection at a low dose of Ivermectin conferred no advantage on LD lines when re-exposed to the low-dose environment for 75 h. However, HD-selected lines showed higher survivorship relative to Z lines on exposure to the high-drug dose.…”
Section: Discussionmentioning
confidence: 92%
“…; Shi et al. ), and that varying the level of under‐dosing may affect the rate at which resistance evolves (Busi and Powles ). Our data suggest that selection at a low dose of Ivermectin conferred no advantage on LD lines when re‐exposed to the low‐dose environment for 75 h. However, HD‐selected lines showed higher survivorship relative to Z lines on exposure to the high‐drug dose.…”
Section: Discussionmentioning
confidence: 99%